1980
DOI: 10.1037/0022-3514.39.1.165
|View full text |Cite
|
Sign up to set email alerts
|

Competition of internal and external information in an exercise setting.

Abstract: During physical exercise, individuals have access to internal sensory and external environmental cues that compete for attentional focus. Two experiments examined when attention to external cues attenuates the perception of physical symptoms and fatigue. In Experiment 1, subjects' physical performance was held constant during exercise on a treadmill. Subjects hearing distracting sounds reported less fatigue and fewer symptoms than subjects hearing an amplification of their own breathing. In Experiment 2, subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
168
2
4

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 242 publications
(181 citation statements)
references
References 4 publications
7
168
2
4
Order By: Relevance
“…Second, additional analysis of the coping balance revealed that depression and somatic complaints are related to the physiological but not the emotional scale. This outcome seems to undermine Pennebaker's rivalry hypothesis (Pennebaker & Lightner, 1980;Pennebaker & Skelton, 1981). However, the Coping Focus Questionnaire may be limited in revealing this kind of rivalry because an emotional point of view, which might have escaped somebody's attention in normal circumstances, could be hard to ignore when explicitly asked about.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Second, additional analysis of the coping balance revealed that depression and somatic complaints are related to the physiological but not the emotional scale. This outcome seems to undermine Pennebaker's rivalry hypothesis (Pennebaker & Lightner, 1980;Pennebaker & Skelton, 1981). However, the Coping Focus Questionnaire may be limited in revealing this kind of rivalry because an emotional point of view, which might have escaped somebody's attention in normal circumstances, could be hard to ignore when explicitly asked about.…”
Section: Discussionmentioning
confidence: 80%
“…A focus on somatic sensations and explanations inhibits attention to the emotional, external situation. This process can be demonstrated empirically (Pennebaker, 1982;Pennebaker & Lightner, 1980;Pennebaker & Skelton, 1981).…”
Section: Introductionmentioning
confidence: 99%
“…The competition between external and internal cues is then resolved by an attentional priority for external cues, resulting in the perception of less bodily symptoms. Investigating the idea of competition between internal and external cues, Pennebaker and Lightner 21 found that joggers running 1800 m in an environment with multiple external information (cross country) were faster than joggers running 1800 m in an environment lacking in external information (lap track) in the absence of differences in perceived fatigue and bodily symptoms. As there were indications that joggers had set their pace in line with their perception of fatigue and bodily symptoms, faster running in joggers running cross country was explained by a diminished perception of fatigue and bodily symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…10,17 -20 It is possible that attentional distraction facilitates perseverance of physical activity. In one of the first papers on the relationship between attentional distraction and physical activity, Pennebaker and Lightner 21 reported two experiments with students. In a field experiment they found that focusing attention on external stimuli while running led to faster running compared to the processing of internal stimuli while running.…”
Section: Introductionmentioning
confidence: 99%
“…Environments featuring plant richness can promote children's and adults' enthusiasm for exercise [3] [4], and make them voluntarily extend the time of exercise [5]. Strolling through forests can substantially increase the activity of natural killer cells and the quantity of anti-cancer active proteins, and decrease the secretion of adrenal hormones.…”
Section: Improving Body Functionsmentioning
confidence: 99%